Ichthyoplankton Species Composition and Assemblages From the Estuary to the Hukou Section of the Changjiang River - Fang, Di-an; Xue, Xiang-ping; Xu, Dong-po; Wang, Xiao-hao; Sun, Ning-ze; Zhang, Bai-dong; Ren, Peng (Frontiers in Marine Science, 2021)
Estuary-river-lake (ERL) complex is critical for the development of ichthyoplankton, which plays an essential role in breeding, nursing and recruitment of freshwater fish species. In this study, different ERL sections were selected to investigate the detail of ichthyoplankton assemblage from the estuary to Hukou section between May to August 2018–2020. During the study period, fish larvae of 40, 35, 54, and 46 fish species were sampled in the Rugao, Nanjing (nearby estuary), Anqing and Hukou (connected river-lake) sections in the Changjiang River, respectively. Results on ichthyoplankton surveys revealed fluctuating assemblage patterns in the different river section; larval fish species composition presented ecological habitat-dependent characteristic, which supported the importance of ERL complex for ichthyoplankton development. Furthermore, the abundance of fish larvae was negatively correlated with water transparency but positively correlated with water temperature, daily rate of water level increase, and runoff in the limitative range. A generalized additive model analysis indicated that the hydrological factors most significantly affecting larval fish abundance are water temperature, transparency, daily rate of water level increase, and runoff (p<0.05). These results also indicated that river estuaries and river-lake connected complex are essential for ichthyoplankton recruitment and migration. Combining with the historical record, ichthyoplankton assemblage’s patterns in the Changjiang River lower reaches were preliminarily illuminated, although additional works are needed such as assessing effects on their survival and recruitment.